2008
DOI: 10.5194/hessd-5-323-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discharges of past flood events based on historical river profiles

Abstract: Abstract. This paper presents a case study to estimate peak discharges of extreme flood events of Neckar River in south-western Germany during the 19th century. It was carried out within the BMBF research project RIMAX (Risk Management of Extreme Flood Events). The discharge estimations were made for the flood events of 1824 and 1882 based on historical cross profiles. The 1-D model Hydrologic Engineering Centers River Analysis System (HEC-RAS) was applied with different roughness coefficients. The results are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…This shows the necessity to resort to modern-day spatially high resolution data and comparable precipitation patterns in order to overcome the drawbacks of the historical meteorological data. The peak flood discharge simulation along the river channel of the Neckar River shows that the discharges derived from different independent sources correspond well, apart from three cross profiles in the upper Neckar section, where the hydraulic simulations produced outliers (Sudhaus et al, 2008). The historical discharge calculations from 1896 (which are based upon the river morphology at that time) as well as the LARSIM simulation using historical meteorological data and the current river morphology, yield discharges which correspond to a HQ 100.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This shows the necessity to resort to modern-day spatially high resolution data and comparable precipitation patterns in order to overcome the drawbacks of the historical meteorological data. The peak flood discharge simulation along the river channel of the Neckar River shows that the discharges derived from different independent sources correspond well, apart from three cross profiles in the upper Neckar section, where the hydraulic simulations produced outliers (Sudhaus et al, 2008). The historical discharge calculations from 1896 (which are based upon the river morphology at that time) as well as the LARSIM simulation using historical meteorological data and the current river morphology, yield discharges which correspond to a HQ 100.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions during the flood event in the river channel (scour, fill, debris) as well as the adjacent flood plain are difficult to determine and thus have a factor of uncertainty. A study by Sudhaus et al (2008) however has shown, that the best results are obtained by using standard values from HEC-RAS (river bed roughness 0.03, floodplain roughness (high grass cover) 0.035).…”
Section: Hydraulic Modeling Of Historical Dischargesmentioning
confidence: 99%
See 3 more Smart Citations